BATIK TRAINING FOR KINDERGARTEN TEACHERS THROUGHOUT MOJOLABAN SUB DISTRICT OF SUKOHARJO REGENCY TO IMPROVE CHARACTER EDUCATION LEARNING FOR THE NATION GENERATION - - Sawitri; - Pujiyana; Mas Sukardi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Many adverse events befall our nation today, including high criminality rate, corruption case rate,  and poor law enforcement. These events make our nation as if encountering prolonged ethic and self-confidence crises. Considering the reality, value/moral education is actually required, based on argument that there is a profound and urgent need. In Permendiknas (National EducationMinister’s Regulation) No.45/2006 each SKL formulation implicitly and explicitly contains value/character substances. Kindergarten teachers throughout Mojolaban Sub District of Sukoharjo Regency have large role and responsibility in relation to educating the children whohave no knowledge and experience because kindergarten children newly know education. Learningshould be consistent with KTSP (Education Unit Level Curriculum) and curriculum has standardto be achieved. Kindergarten teachers throughout Mojolaban Sub District with the stipulation to be complied with have not been able to implement it maximally. They have not had it yet. The problems the partners encountered included: The Kindergarten teachers throughout Mojolaban Sub District have not had experience yet in batik learning that can grow cultural education aspects in providing character education to the nation generation. In this activities, the object of training were Kindergarten teachers throughout Mojolaban Sub District consisting of 15 teachers with training duration for 4 hours conducted on April 2014 at 08.00 a.m. to 02.00 p.m. The result of training showed that 85% of kindergarten teachers throughout Mojolaban Sub District had beenable to produce batik in producing handkerchief, cloth, batik for dressing tissue container, and other handicraft and only 15% of them were incapable of producing batik. It was because of age factor so that the participants were difficult to understand the presenter’s explanation so  anddifferent patience and persistence levels from one person to another, but it had belonged to successful category because only 15% of teachers did not master in pretest and in the posttest it improved very significantly consistent with the presenter’s expectation. This training could be used as the example for cultural art-based learning to develop the nation generation character education.Keywords: Training, Batik, Nation generation character education.